Effects of educational technology on reading achievement for Chinese K-12 English second language learners: A meta-analysis - Ni, Aohua; Cheung, Alan C. K.; Shi, Jieping (Frontiers in Psychology, 2022)
No systematic published research has reviewed the impact of educational technology on English reading outcomes targeting the Chinese-speaking population. Therefore, this review intended to examine the impact of educational technology and its alternative types on reading achievement for Chinese English second language learners (ESLs) to understand how to best use technology applications to facilitate reading instruction. A total of 35 qualified studies were included in our analysis covering a sample size of 7,989 Chinese K-12 participants. Consistent with previous meta-analyses, our findings indicated a modest positive impact of educational technology on reading outcomes compared with the traditional teaching method (d = +0.37). For the five types of intervention identified in this review, we found that the comprehensive model had the largest impact (d = +0.60), followed by social media tools (d = +0.46), integrated online-learning system (d = +0.31), and multimedia-transmission model (d = +0.27). However, supplementary activities did not generate educationally meaningful effects on reading outcomes for Chinese ESLs (d = +0.05). The impacts of different moderators, implications, and limitations were also discussed. We argue for further integrating technology with the existing curriculum and pedagogy. The study adds to the second language (L2) reading literature corpus.